Psychedelic‐assisted therapy for functional neurological disorders: A theoretical framework and review of prior reports. Issue 6 (5th December 2020) - Stewart, Benjamin; Dean, Jon G.; Koek, Adriana; Chua, Jason; Wabl, Rafael; Martin, Kayla; Davoodian, Naveed; Becker, Christopher; Himedan, Mai; Kim, Amanda; Albin, Roger; Chou, Kelvin L.; et al.
Abstract: Functional neurological disorders (FNDs), which are sometimes also referred to as psychogenic neurological disorders or conversion disorder, are common disabling neuropsychiatric disorders with limited treatment options. FNDs can present with sensory and/or motor symptoms, and, though they may mimic other neurological conditions, they are thought to occur via mechanisms other than those related to identifiable structural neuropathology and, in many cases, appear to be triggered and sustained by recognizable psychological factors. There is intriguing preliminary evidence to support the use of psychedelic‐assisted therapy in a growing number of psychiatric illnesses, including FNDs. We review the theoretical arguments for and against exploring psychedelic‐assisted therapy as a treatment for FNDs. We also provide an in‐depth discussion of prior published cases detailing the use of psychedelics for psychosomatic conditions, analyzing therapeutic outcomes from a contemporary neuroscientific vantage as informed by several recent neuroimaging studies on psychedelics and FNDs.